2020
DOI: 10.31235/osf.io/jy8fn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in Parents’ Domestic Labor During the COVID-19 Pandemic

Abstract: In late April 2020, we surveyed 1,060 U.S. parents in residing with a partner of a different sex in order to examine how divisions of housework and childcare may have changed since the beginning of the COVID-19 pandemic.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(134 citation statements)
references
References 41 publications
11
112
0
7
Order By: Relevance
“…We explored these questions by asking a representative sample of Hungarians (Inequalities during the Coronavirus in Hungary Survey Research) about the changes in the domestic division of labour, including childcare, in their households in May 2020. In line with the few available preliminary empirical analyses about the effect of COVID on the gender division of childcare work in the US (Carlson et al 2020), Canada (Shafer et al 2020), Australia (Craig and Churchill 2020;Craig 2020) and Israel (Herzberg-Druker et al 2020), we found that in Hungary men, on average, have increased their contributions to at roughly the same rate as women did. However, given that women had been putting in many more hours of childcare work than men before the pandemic, their workload, and especially the workload of highly educated mothers, grew significantly more than men's resulting in a widening of the childcare gender gap after March 2020.…”
Section: Introductionsupporting
confidence: 89%
“…We explored these questions by asking a representative sample of Hungarians (Inequalities during the Coronavirus in Hungary Survey Research) about the changes in the domestic division of labour, including childcare, in their households in May 2020. In line with the few available preliminary empirical analyses about the effect of COVID on the gender division of childcare work in the US (Carlson et al 2020), Canada (Shafer et al 2020), Australia (Craig and Churchill 2020;Craig 2020) and Israel (Herzberg-Druker et al 2020), we found that in Hungary men, on average, have increased their contributions to at roughly the same rate as women did. However, given that women had been putting in many more hours of childcare work than men before the pandemic, their workload, and especially the workload of highly educated mothers, grew significantly more than men's resulting in a widening of the childcare gender gap after March 2020.…”
Section: Introductionsupporting
confidence: 89%
“…Early research by Carlson, Petts, and Pepin (2020) of parents in the United States indicates that COVID‐19 is both exacerbating and reducing gender inequalities in the domestic division of labor among heterosexual couples with children. As with before the pandemic, mothers are holding primary responsibility for housework and childcare in most families during this time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to social norms and the structure of the workforce, COVID-19 has created an additional burden for women to care for and homeschool their children (UN 2020). Carlson et al (2020) surveyed 1,060 US parents living with a partner of a different sex in April 2020 and found that 50% of families reported that homeschooling was the responsibility of mothers. Meanwhile, 12% reported that it was the responsibility of fathers, 28% reported that both parents were responsible, and 10% reported that they relied on other sources for homeschooling.…”
Section: 3%)mentioning
confidence: 99%